Factors Relating to Choosing a Delivery Help for Pregnant Women in Lantosan Village Padang Bolak District Padang Lawas Utara District - Harahap, Ica Fauziah; Rambe, Kumala Sari; Pohan, Melia Shintia Mutiara (LLDIKTI Wilayah 1, 2024)
Childbirth is an important and always memorable event in a woman's life. Every woman has her own birth experience that she can share with others. Based on the results of Basic Health Research (Riskesdas), births assisted by competent health workers were 70.4%, but 29.6% were carried out by non-health workers/quacks. The aim of this research was to analyze factors related to mothers in choosing birth attendants in Lantosan village. This research is a descriptive analysis research using a cross sectional research design. The population in this study was all 45 pregnant women domiciled in Lantosan village with a sampling technique, namely total sampling. The research results showed that there was a relationship between education, knowledge, attitudes, accessibility, economic status and family support in selecting a birth attendant with a p value of 0.000. It is hoped that pregnant women will actively check their pregnancies, carry out pregnancy consultations and assist with childbirth by health workers